The performance of discrete models of low reynolds number swimmers - Qixuan Wang; Hans G. Othmer (Mathematical Biosciences and Engineering)
Swimming by shape changes at low Reynolds number is widely used in biology andunderstanding how the performance of movement depends on the geometric pattern ofshape changes is important to understand swimming of microorganisms and in designing lowReynolds number swimming models. Thesimplest models of shape changes are those that comprise a series of linkedspheres that can change their separation and/or their size. Herein we comparethe performance of three models in which these modes are used in different ways.